Differences in neuronal ciliation rate and ciliary content revealed by systematic imaging-based analysis of hiPSC-derived models across protocols - Haenseler, Walther; Eschment, Melanie; Evans, Beth; Brasili, Marta; Figueiro-Silva, Joana; Roethlisberger, Fee; Abidi, Affef; Jackson, Darcie; Müller, Martin; Cowley, Sally A.; Bachmann-Gagescu, Ruxandra (Frontiers in Cell and Developmental Biology, 2025)
IntroductionCiliopathies are a group of human Mendelian disorders caused by dysfunction of primary cilia, small quasi-ubiquitous sensory organelles. Patients suffering from ciliopathies often display prominent neurodevelopmental phenotypes, underscoring the importance of primary cilia during development and for function of the central nervous system (CNS). Human tissues, in particular from the CNS, are very hard to obtain for research. Patient derived- or genetically engineered human induced pluripotent stem cells (hiPSCs) are therefore a precious resource for investigating the role of cilia in human neurons.MethodsIn this study we used a variety of 2D and 3D neuronal differentiation protocols in multiple hiPSC lines and systematically analyzed ciliation rates and ciliary length in hiPSCs, neural stem cells (NSCs), immature and different types of mature neurons using immunofluorescence.ResultsWe found that ciliation rate varied substantially between cell lines and differentiation protocols. Moreover, ciliation rate depended on differentiation stage, being maximal in NSCs and decreasing with neuronal maturation. In various types of mature neurons obtained with different protocols, we found ciliation rates to be as low as ∼10%. Neuronal density also played an important role, with higher ciliation in denser cultures. We further investigated the ciliary protein content in these cells at different differentiation stages using commonly used antibodies against ARL13B, INPP5E, AC3 and GPR161. Cilia in hiPSCs, NSCs and neurons were all positive for ARL13B, with a decreasing trend in intensity in more mature neurons. Likewise, INPP5E was present in all cilia analyzed, while AC3 positivity increased as maturation proceeded. Interestingly, we found that while GPR161 signal almost completely disappeared from cilia upon Sonic hedgehog (SHH) stimulation in NSCs and immature neurons, this was not the case in more mature neurons, suggesting a possible developmental time window for cilia-dependent SHH signaling.ConclusionTaken together, our results provide a systematic description of cilia in hiPSC-derived neuronal cells generated with different protocols, underscoring the importance of selecting the optimal model system and controls for investigating primary cilia in hiPSC-derived neuronal cells.